Respostas
respondido por:
3
a1-a1
0-(-3)=3
r=3 <<<<<
0-(-3)=3
r=3 <<<<<
respondido por:
5
Olá!!!
Resolução!!!
PA ( - 3, 0, 3, ... )
........a1, a2, a3, ...
a2 = a1 + r
0 = - 3 + r
- 3 + r = 0
r = 0 + 3
r = 3
R = A razão da PA é 3
Espero ter ajudado!!!
Resolução!!!
PA ( - 3, 0, 3, ... )
........a1, a2, a3, ...
a2 = a1 + r
0 = - 3 + r
- 3 + r = 0
r = 0 + 3
r = 3
R = A razão da PA é 3
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás